1998
DOI: 10.1175/1520-0469(1998)055<2715:citchs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Convection in TOGA COARE: Horizontal Scale, Morphology, and Rainfall Production

Abstract: The occurrence frequency and rainfall production of mesoscale convective systems (MCSs) relative to smaller groups of convective clouds over the tropical oceans is not well known. Eighty days of shipboard radar data collected during the recent Tropical Ocean Global Atmosphere Coupled Ocean-Atmosphere Response Experiment (TOGA COARE) were used to provide a detailed view of convection in the western Pacific warm pool, a region of global climatological significance. The aim of this study was to document the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
119
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 38 publications
16
119
2
Order By: Relevance
“…However, a dissimilarity is also observed between our case study and TOGA COARE. During TOGA COARE, mesoscale convective events are observed 2-5 days after the maximum of the westerly wind burst (Rickenbach and Rutledge, 1998). However, in our case study, a well-organized convective event is not observed during the postwesterly wind burst phase of the ISV (Period 3).…”
Section: Temporal Variations Of Ir Blackbody Brightness Temperature Ocontrasting
confidence: 61%
See 1 more Smart Citation
“…However, a dissimilarity is also observed between our case study and TOGA COARE. During TOGA COARE, mesoscale convective events are observed 2-5 days after the maximum of the westerly wind burst (Rickenbach and Rutledge, 1998). However, in our case study, a well-organized convective event is not observed during the postwesterly wind burst phase of the ISV (Period 3).…”
Section: Temporal Variations Of Ir Blackbody Brightness Temperature Ocontrasting
confidence: 61%
“…Lau et al, 1989) and observational studies over the western Pacific during TOGA COARE (Rickenbach and Rutledge, 1998;Lin and Johnson, 1996). Moderate vertical shear of horizontal wind (20-30 m s −1 ) plays an important role in the organization of mesoscale convective activities with a horizontal scale of >100 km (Saxen and Rutledge, 2000;Rickenbach and Rutledge, 1998).…”
Section: Temporal Variations Of Ir Blackbody Brightness Temperature Omentioning
confidence: 99%
“…Their methods are aimed at assessing the natural variability of the WAM over long periods. However, such generalization may deserve some care since precipitations are known to have patchy features with small spatial scale (Houze and Cheng, 1977;Leary and Houze, 1979;Nicholson, 1995;Chen et al, 1996;Rickenbach and Rutledge, 1998;Lebel et al, 2009). In this study, we show how the local Saloum rainfall is coherent with the regional Sahel rainfall at seasonal to decadal time scales.…”
Section: Oceanic Forcings Of the Wammentioning
confidence: 65%
“…While their work opens stimulating perspectives for the investigation of the seasonality of the WAM in the past, the relationship between local and regional rainfall variability needs to be assessed before extending paleoclimate reconstructions in the Saloum to the WAM in general. Precipitation is indeed known to be a patchy feature with small spatial scale (e.g., Houze and Cheng, 1977;Leary and Houze, 1979;Nicholson, 1995;Chen et al, 1996;Rickenbach and Rutledge, 1998;Lebel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, an isolated thunderstorm is an example of IPF organization, while mesoscale convective systems or widespread frontal rain are examples of MPF organization. A similar framework has been used for climatological studies of precipitation systems regionally and globally using surface and space-based radar observations [8][9][10][11][12][13]. Differences in the organization of precipitating systems reflect the influence of the large-scale environment, for example, squall line mesoscale convective systems tend to form in environments of high shear and moderate convective available potential energy [14].…”
Section: Introductionmentioning
confidence: 99%